2006
DOI: 10.1007/s00432-006-0154-0
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent use of vinorelbine and gefitinib induces supra-additive effect in head and neck squamous cell carcinoma cell lines

Abstract: This finding is encouraging as a proof of the possible benefit of combing an EGFR targeting compound with a cell cycle specific drug and warrants further studies of available combinations in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…31 Early studies on HNSCC cell lines used much higher doses than this 32 while more recent studies all have used doses below 2 μM gefitinib. 33,34 The relative insensitivity of the cell line to gefitinib in combination with the development of their relative efficiencies in the nucleus are unknown. siRNAs exert their effect mainly in the cytoplasm of cells, 37 but if efficient will reduce nuclear as well as membranous and cytoplasmic receptor levels.…”
Section: Discussionmentioning
confidence: 99%
“…31 Early studies on HNSCC cell lines used much higher doses than this 32 while more recent studies all have used doses below 2 μM gefitinib. 33,34 The relative insensitivity of the cell line to gefitinib in combination with the development of their relative efficiencies in the nucleus are unknown. siRNAs exert their effect mainly in the cytoplasm of cells, 37 but if efficient will reduce nuclear as well as membranous and cytoplasmic receptor levels.…”
Section: Discussionmentioning
confidence: 99%
“…Gefitinib and vinorelbine combinations have been investigated previously in preclinical studies using tumor cell line models of head and neck squamous cell carcinoma (HNSCC) and NSCLC. 58,59 In a panel of six HNSCC tumor cell lines, the combination of gefitinib plus vinorelbine had a supra-additive cytotoxic effect in four of six cell lines, and additive cytotoxic effects in the other two cell lines. 58 Gefitinib and vinorelbine are both metabolized by the CYP3A4 P450 isoenzyme, and when co-administered in vivo, drug-drug interactions may alter their respective exposure levels.…”
Section: Discussionmentioning
confidence: 99%
“…58,59 In a panel of six HNSCC tumor cell lines, the combination of gefitinib plus vinorelbine had a supra-additive cytotoxic effect in four of six cell lines, and additive cytotoxic effects in the other two cell lines. 58 Gefitinib and vinorelbine are both metabolized by the CYP3A4 P450 isoenzyme, and when co-administered in vivo, drug-drug interactions may alter their respective exposure levels. 58 In 17 NSCLC cell lines that included 4 that overexpressed P-glycoprotein (Pgp/MDR1) and 3 with sensitizing EGF-R mutations, combinations of gefitinib with vinorelbine exhibited synergism (mean CIs <1) in cell lines without sensitizing EGF-R mutations.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][27][28][29] Only limited data are currently available on the efficacy of combining VNB with GEF on NSCLC to treat in vitro and in vivo models. Erjala et al 26 have shown that the concomitant use of VNB and GEF induced both an additive and a supra-additive cytotoxic effect in six different head and neck SCC cell lines, whereas studies in vivo have shown that the combination of GEF with VNB was active but not well tolerated. 37,38 Tsai et al demonstrated synergism in combining GEF with antimicrotubule agents using a panel of 12 NSCLC cell lines that had no sensitizing EGFR mutations (SEM).…”
Section: Discussionmentioning
confidence: 99%
“…Erjala et al have evaluated the efficacy of the concomitant treatment of VNB and GEF in cell lines of primary squamous cell carcinoma (SCC) of the head and neck, and a clear additive or supra-additive effect was demonstrated. 26 Moreover, in vitro experiments have shown that the antitumor effects that are produced by administering GEF in combination with chemotherapy are both enhanced and dependent on the sequence of treatment. 27,28 On the contrary, controversial data on disease-free survival rates were found when using the sequential treatment of GEF or erlotinib with chemotherapy in advanced NSCLC patients in phase II clinical studies.…”
mentioning
confidence: 99%